Purification of KBF1, a common factor binding to both H-2 and beta 2-microglobulin enhancers. - Yano, O (1987)
An enhancer binding factor, designated KBF1, has been purified from the nuclear extract of mouse BW5147 thymoma cells by five column chromatography steps including a sequence-specific DNA affinity column. Gel retardation and footprint analysis have shown that purified KBF1 has a binding activity specific for both H-2 and beta 2-microglobulin enhancer sequences. After SDS-polyacrylamide gel electrophoresis of the most purified preparation a 48-kd protein showed, after elution and renaturation, a binding activity to both enhancer sequences. These findings suggest that the expression of both H-2 and beta 2-microglobulin genes utilizes a common regulatory mechanism.